Participatory co-creation of an adapted physical activity program for adults with moderate-to-severe traumatic brain injury - Quilico, Enrico; Wilkinson, Shawn; Duncan, Lindsay; Sweet, Shane; Bédard, Evelyne; Trudel, Eric; Colantonio, Angela; Swaine, Bonnie (Frontiers in Rehabilitation Sciences, 2022)
Background: Research about using physical activity (PA) to improve health, quality of life, and participation after moderate-to-severe traumatic brain injury (TBI) is receiving growing attention. However, best-practices for maintaining PA participation after TBI have yet to be defined. In this context, a team of researchers and stakeholders with a moderate-to-severe TBI (including program participants and peer mentors) participated in a co-creation process to optimize a 9-month, 3-phased, community-based, adapted PA program named TBI-Health. Purpose: The study aimed to provide a detailed account of the participation in and co-creation of a new TBI-Health Program to enhance sport and exercise participation for adults with moderate-to-severe TBI. Specifically, we carried out an in-depth exploration of the perceived experiences and outcomes of users over one cycle of the program to assist the co-creation process. Methods: An interpretive case study approach was used to explore the experiences and outcomes of the participatory co-creation within and across phases of the TBI-Health program. A purposeful sample of fourteen adults with moderate-to-severe TBI (program participants n=10; peer mentors n=4) were involved in audio-recorded focus groups after each program phase. Reflexive thematic analyses within and across the phases identified three higher-order themes. Results: Program Participation included barriers, facilitators, sources of motivation and suggested modifications to optimize the program; Biopsychosocial Changes highlighted perceived physical, psychological, and social outcomes, by self and others, that resulted from program participation; PA Autonomy emphasized transitions in knowledge, sex- and gender-related beliefs, and abilities related to exercise and sport participation. Conclusions: Study findings suggest the TBI-Health program can increase autonomy for and reduce barriers to PA for adults with moderate-to-severe TBI, which results in increased PA participation and important physical, psychological, and social benefits. More research is needed about the TBI-Health program with larger samples.